Spectral dependence of aerosol light absorption over Camaguey, obtained from an integrating sphere spectral system - Mogo, Sandra; Barja Gonzalez, Boris; Cachorro, Victoria; Barroso, Raquel; Monteiro, Rafhael; de Frutos, Angel; Estevan, Rene; Carlos Antuna, Juan (My University, 2019)
Atmospheric aerosol particles were collected at Camaguey (21.42 degrees N, 77.85 degrees W, 122 m asl), Cuba, during 2010 and 2012-2014, for investigating the absorption of light by particles, particulate matter (PM) concentration, and elemental composition. Samples were collected with a low volume particulate Dekati PM10 impactor twice a week with a collection time of 24 hours. The sample flow rate was 15 1/min. Gravimetric analysis of the particulate matter fractions PM1 (PM< 1 pm) was carried out for 104 samples. An Integrating Sphere Spectral System (IS3) was developed for measuring the spectral absorption coefficient from the UV to the visible wavelengths with a spectral resolution of 10 nm. The system uses a filter-based method. The light absorption is determined by measuring and comparing the intensity of light transmitted by filters with and without particles deposited. The IS3 is fully described in this work. It consists of a 6-inch integrating sphere with a spectral reflectance of 98 % that covers the wavelength range from 250 to 2500 nm. The light source includes a 150 W xenon lamp included in an ORIEL APEX illuminator equipped with a transmission filter, and an automated scanning monochromator. The signal is detected by a compact size Si detector (200-1100 nm) connected to a light meter. With this approach continuous spectra of the absorption coefficients in the 320-800 nm spectral range can be obtained with variable spectral resolution. Spectral absorption coefficients measured by the IS3 are presented and analyzed for the campaign period.
Keywords: aerosols; optical properties; absorption coefficients; absorption angstrom coefficient; integrating sphere